Endodontic Flare-up Incidense in Irreversible Pulpitis in Universitas Airlangga Dental Hospital (RSKGMP Universitas Airlangga) - Galih Sampoerno; Sukaton; Salwa Aulia Rahmawati (Conservative Dentistry Journal, 2022)
Background: Carious lesions that do not be treated, becomes infected and inflamed, leading to irreversible pulpitis. One of the treatments for irreversible pulpitis is root canal treatment. In root canal treatment can cause flare-ups. Purpose: Obtaining a data base on flare-ups with a diagnosis of irreversible pulpitis at RSKGMP and obtaining a picture of flare-ups in irreversible pulpitis based on root canal preparation techniques, root canal irrigation materials, root canal dressing materials, and root canal obturation techniques. Methods: The study used was a descriptive observational study with a study design cross sectional in patients with a diagnosis of irreversible pulpitis who had received root canal treatment at the UPF Dental Conservation RSKGMP University of Airlangga in 2018, 2019, and 2020. Results: A total of 14 patients (28%) of 50 patients experienced (flare-up). Conclusion: The incidence flare-ups of root canal treatment in irreversible pulpitis at RSKGMP University of Airlangga is 28%.